2016
DOI: 10.1016/j.jmaa.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

On the drawdowns and drawups in diffusion-type models with running maxima and minima

Abstract: This document is the author's final accepted version of the journal article. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.On the drawdowns and drawups in diffusion-type models with running maxima and minima Pavel V. Gapeev * Neofytos Rodosthenous † To appear in Journal of Mathematical Analysis and ApplicationsWe obtain closed-form expressions for the values of joint Laplace transforms of the running maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…(ii) Let us now assume that λ i > λ 1−i = 0 holds, for any i = 0, 1 fixed. In this case, by using straightforward calculations from part (i) of Subsection 3.2, it can be shown that the candidate solution of the system in (5.3)-(5.9) takes the form: 18) for k = 1, 2, where the value b * 1−i is determined by the equation: 19) for i = 0, 1 (see [8]). Substituting the expression for W 1−i (x, s; b * 1−i ) from (5.17) into the equation of (5.3) for W i (x, s) and applying the conditions of (5.4)-(5.6), we obtain that the candidate value function admits the representation:…”
Section: Solution To the Free-boundary Problemmentioning
confidence: 99%
“…(ii) Let us now assume that λ i > λ 1−i = 0 holds, for any i = 0, 1 fixed. In this case, by using straightforward calculations from part (i) of Subsection 3.2, it can be shown that the candidate solution of the system in (5.3)-(5.9) takes the form: 18) for k = 1, 2, where the value b * 1−i is determined by the equation: 19) for i = 0, 1 (see [8]). Substituting the expression for W 1−i (x, s; b * 1−i ) from (5.17) into the equation of (5.3) for W i (x, s) and applying the conditions of (5.4)-(5.6), we obtain that the candidate value function admits the representation:…”
Section: Solution To the Free-boundary Problemmentioning
confidence: 99%
“…are continuous uniformly integrable martingales under the probability measure P, when α < 0 and α > 0, respectively. Note that the processes S and Q may change their values only at the times when X t = S t and X t = Q t , for t ≥ 0, respectively, and such times accumulated over the infinite horizon form the sets of the Lebesgue measure zero, so that the indicators in the expressions of ( 15)-( 16) and ( 17)- (18)…”
Section: The Optimal Stopping Problemsmentioning
confidence: 99%
“…Discounted optimal stopping problems for the running maxima and minima of the initial continuous (diffusion-type) processes were initiated by Shepp and Shiryaev [44] and further developed by Pedersen [36], Guo and Shepp [24], Gapeev [14], Guo and Zervos [25], Peskir [39,40], Glover, Hulley, and Peskir [22], Gapeev and Rodosthenous [17][18][19], Rodosthenous and Zervos [43], Gapeev, Kort, and Lavrutich [20], and Gapeev and Al Motairi [15] among others. It was shown, by means of the maximality principle for solutions of optimal stopping stopping problems established by Peskir [37], which is equivalent to the superharmonic characterization of the value functions, that the optimal stopping boundaries are given by the appropriate extremal solutions of certain (systems of) first-order nonlinear ordinary differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…The distributional properties of Ta and MTa are also studied in Douady, Shiryaev, and Yor () and Magdon‐Ismail, Atiya, Pratap, and Abu‐Mostafa (). Furthermore, studies that involve both the drawdown and drawup processes have been done by Popisil, Vecer, and Hadjiliadis (), Zhang and Hadjiliadis () and Gapeev and Rodosthenous (). This stopping time is commonly referred to as drawdown time in the literature but we note the distinction between this and τD.…”
Section: Introductionmentioning
confidence: 99%